Understanding Vasculitis: A Detailed Exploration of Clinical Manifestations and Management - Rohit Raina; Preeti Singh Dhoat; Niket Verma; Sakshi (Medicine Essentials in Clinical Practice, 2025)
Vasculitis is a disease process that is characterized by inflammation of and damage to blood vessels, which produces narrowing and usually occlusion of blood vessels. The symptoms and signs of vasculitis are the result of the particular tissues or organs that are undergoing ischemia or infarction from the narrowing or occlusion of blood vessels. Understanding the pathophysiology and pathogenesis is also vital; major pathogenic mechanisms involve immune complex formation, as well as antineutrophil cytoplasmic antibodies (ANCA). This review focuses on discussing various types of vasculitis and their available treatment process.